SERIOUS CRIMES AMONG MINORS: CAUSES, TRENDS, AND PREVENTIVE MECHANISMS (World Bulletin of Management and Law, 2025)
This research paper provides a comprehensive analysis of serious crimes committed by minors, drawing upon interdisciplinary perspectives from criminology, sociology, psychology, and education sciences. Using 2025 academic sources as the basis for the literature review, the study examines the determinants of violent and serious criminal behaviors among juveniles, including family dysfunction, social disorganization, digital influences, psychological instability, and the deterioration of educational environments. Particular emphasis is placed on the increasing severity of juvenile crime, the rise of group-based violent actions, and the growing involvement of younger adolescents.